Future Pharmacists' Opinions on the Facilitation of Self-Care with Over-the-Counter Products and Whether This Should Remain a Core Role - Lezley-Anne Hanna; Alana Murphy; Maurice Hall; Rebecca Craig (MDPI AG, 2021)
Background: The aim was to investigate pharmacy students' views on the role of the pharmacist in facilitating self-care with over-the-counter (OTC) medicines, particularly in light of new roles, and establish personal practice. Methods: Final year pharmacy students at Queen's University Belfast were invited to participate. Data were collected via a pre-piloted questionnaire, distributed at a compulsory class (only non-identifiable data were requested). Descriptive statistics were performed, and non-parametric tests were employed for inferential statistical analysis (responses by gender). Results: The response rate was 87.6% (78/89); 34.6% (27/78) males and 65.4% (51/78) females. Over a third [34.6% (27/78)] reported using OTC medicines about once a month. All appreciated the importance of an evidence-based approach to optimize patient care. Most [(96.2% (75/78)] deemed OTC consultations should remain a fundamental responsibility of pharmacists and 69.2% (54/78) thought OTC consultations have the potential to be as complex as independent pharmacist prescribing. Females felt more confident recommending OTC emergency contraception than males (p = 0.002 for levonorgestrel and p = 0.011 for ulipristal acetate). Many [61.5% (48/78)] considered more medicines should not be deregulated from prescription-only status. Conclusions: Data from this single institution suggests that enabling self-medication is an important part of practice but there were confidence issues around deregulations.